Non-isolated LLC resonant DC-DC converter with balanced rectifying current and stress - Abdulhakeem Mohammed Dobi; Mohd Rodhi Sahid (Indonesian Journal of Electrical Engineering and Computer Science, 2020)
In isolated type LLC resonant converters, transformer leakage inductances can be merged with the resonant inductor to extend the ZVS capability of the switches apart from isolation and voltage scaling. However, the transformer presents a resonant imbalance in the secondary side leading to secondary current unbalance, an increase in RMS value of the secondary current and increase thermal stress. This paper proposed a half-bridge non-isolated LLC resonant converter with a balanced rectifying current and stress in the rectifier diodes. The proposed converter can achieve the most advantages of isolated LLC converters, such as ZVS and low MOSFET turn-off loss. By the non-isolation method, secondary current and, transformer loss is significantly reduced. In addition, rectifier diodes operate with zero current switching and balanced rectifying current and stress over the entire operating range. The proposed non-isolated structure is verified by the experimental result with a 60W LLC resonant converter.